2002
DOI: 10.1007/s11663-002-0052-z
|View full text |Cite
|
Sign up to set email alerts
|

Control of heat transfer and growth uniformity of solidifying copper shells through substrate temperature

Abstract: To determine the optimal roll temperature in a twin-roll copper-strip caster, copper blocks preheated between 25 ЊC and 350 ЊC were immersed in a bath of molten copper for 0.5 seconds. A significant increase in the contact heat-transfer coefficient at the substrate-shell interface was obtained when the substrates were heated above 200 ЊC and the gain in the solidified shell thickness was 20 pct. The shell growth was also approximately 35 pct more uniform at a high substrate temperature, and micrographic examin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This arrangement was semi-intrinsic as the substrate acted as one element of the circuit [24,25,36]. Two such thermocouples were used in the tests, one at a depth of approximately 1 mm from the surface, the other at 5 mm, the exact location being measured to a precision of 0.01 mm with a vernier prior to an experimental run.…”
Section: Methodsmentioning
confidence: 99%
“…This arrangement was semi-intrinsic as the substrate acted as one element of the circuit [24,25,36]. Two such thermocouples were used in the tests, one at a depth of approximately 1 mm from the surface, the other at 5 mm, the exact location being measured to a precision of 0.01 mm with a vernier prior to an experimental run.…”
Section: Methodsmentioning
confidence: 99%
“…For example, Murakami et al [34] reported 10% -30% increase in heat flux in the first 5 seconds of the solidification of hypoperitectic steel on a water-cooled chill with 1 -5 mm spaced vertical grooves compared to that on a smooth copper mold. Bouchard et al [27] [28] reported even higher increase in heat flux obtained in the early stages (<0.5 s) of solidification of a copper alloy on a water-cooled sand blasted copper chills and copper chills with 0.5 -2 mm deep vertical grooves with 0.15 -1 mm spacing. This suggests that the observed alleviation of surface lap marks with grooved mold surface topography is not entirely due to moderation of interfacial heat transfer.…”
Section: Effect Of Mold Surface Topographymentioning
confidence: 94%